2007
DOI: 10.1111/j.1365-313x.2007.03374.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of a GDSL lipase‐like protein as sinapine esterase in Brassicaceae

Abstract: SummaryThe seeds of most members of the Brassicaceae accumulate high amounts of sinapine (sinapoylcholine) that is rapidly hydrolyzed during early stages of seed germination. One of three isoforms of sinapine esterase activity (BnSCE3) has been isolated from Brassica napus seedlings and subjected to trypsin digestion and spectrometric sequencing. The peptide sequences were used to isolate BnSCE3 cDNA, which was shown to contain an open reading frame of 1170 bp encoding a protein of 389 amino acids, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 36 publications
(92 reference statements)
1
76
0
1
Order By: Relevance
“…Hydrolysis of the compound in germinating seedlings by sinapoylcholine esterase (SCE) releases choline for phospholipid synthesis and sinapate which is re-esterified by SGT to form sinapoylglucose (Tzagoloff, 1963;Nurmann and Strack, 1979;Strack et al, 1980;Clauß et al, 2008). There are four Arabidopsis genes whose sequences are similar to the gene encoding SCE in B. napus (Clauß et al, 2008).…”
Section: Sinapoylcholine Esterase (Sce)mentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrolysis of the compound in germinating seedlings by sinapoylcholine esterase (SCE) releases choline for phospholipid synthesis and sinapate which is re-esterified by SGT to form sinapoylglucose (Tzagoloff, 1963;Nurmann and Strack, 1979;Strack et al, 1980;Clauß et al, 2008). There are four Arabidopsis genes whose sequences are similar to the gene encoding SCE in B. napus (Clauß et al, 2008).…”
Section: Sinapoylcholine Esterase (Sce)mentioning
confidence: 99%
“…The proteins encoded by these three genes exhibit SCE activity and are highly expressed in 3-day-old seedlings (Table 1). One of these genes (At1g28670) is also expressed in adult leaves, suggesting a possible alternative role in mature plants (Clauß et al, 2008). Interestingly, the three Arabidopsis SCEs are not SCPL proteins like SMT and SCT, but instead are similar in sequence to GDSL serine lipases/esterases, hydrolytic enzymes with broad substrate specificities (Akoh et al, 2004).…”
Section: Sinapoylcholine Esterase (Sce)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the Extraction II, rapeseed meal was extracted with adding of 10% methanol contained 0.1% phosphoric acid together with TBHQ. And hydrochloric acid was then added with different ratios (1:1, 1:2, 1:3, v/v; labeled as EII-A, EII-B, EII-C, respectively) [12]. After each extraction process, the mixtures were centrifuged at 12,000 rpm at 4˚C for 15 min.…”
Section: Acid Hydrolysismentioning
confidence: 99%
“…1A), chrysanthemoyl CoA and (S)-pyrethrolone were added to a crude enzyme from the flower bud, resulting in the production of pyrethrin I. Purifying this enzyme and cloning the gene unexpectedly led to the discovery that the isolated enzyme showed similarities to GDSL lipases/esterases which have been named after the Gly-Asp-Ser-Leu motif. 4) This family consists of many members with such diverse functions as ceramidase, 5) sinapine esterase, 6) transesterification, 7) cutin synthesis 8) and cutinase activities 9) in plants. 10) We confirmed that the recombinant enzyme expressed in Escherichia coli as a fusion with maltosebinding protein (MBP) showed acyltransferase activity for pyrethrin synthesis.…”
mentioning
confidence: 99%